Body Blows Six Performances - Miller, Tim (The University of Wisconsin Press, 2002)
Hailed for his humor and passion, the internationally acclaimed performance artist Tim Miller has delighted, shocked, and emboldened audiences all over the world. Body Blows gathers six of Miller's best-known performances that chart the sexual, spiritual, and political topography of his identity as a gay man: Some Golden States, Stretch Marks, My Queer Body, Naked Breath, Fruit Cocktail, and Glory Box. In Body Blows, Tim Miller leaps from the stage to the page, as each performance script is illustrated with striking photographs and accompanied by Miller's notes and comment. This book explores the tangible body blows-taken and given-of Miller's life and times as explored in his performances: the queer-basher's blow, the sweet blowing breath of a lover, the below-the-belt blow of HIV/AIDS, the psychic blows from a society that disrespects the humanity of lesbian and gay relationships. Miller's performances are full of the put-up-your-dukes and stand-your-ground of such day-to-day blows that make up being gay in America.